Global content marketing : how to create great content, reach more customers, and build a worldwide marketing strategy that works - Didner, Pam (McGraw-Hill Education, 2015)
Technology has virtually erased national borders, forever transforming the way we reach and engage customers, as well as the way we search for and consume content. This book takes you step-by-step through the process of creating and refining your strategies to meet this new reality. You will learn how to create content that engages people--regardless of their country and culture; identify key actions and strategies to apply to your projects; connect "dots" that others don't see and connect them in ways you never thought of before. --